4x-(6x+11)= 5

First we will open the brackets.

==. 4x -6x -11 = 5

Now we will combine like terms.

==> -2x -11 = 5

Now we will add 11 to both sides.

==> -2x = 5+ 11

==> -2x = 16

Now we will divide by -2.

==> x = 16/-2 = -8

**Then, the answer is : x = -8**

## We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

- 30,000+ book summaries
- 20% study tools discount
- Ad-free content
- PDF downloads
- 300,000+ answers
- 5-star customer support

Already a member? Log in here.

Are you a teacher? Sign up now